Application of a Gastroduodenal Artery Graft for Reconstruction of the Hepatic Artery during Radical Resection of Hilar Cholangiocarcinoma. (3rd August 2015) - Liang, Yurong; Wang, Jing; Shi, Xianjie; Dong, Jiahong; Gu, Wanqing
Abstract : This paper was designed to evaluate a novel surgical procedure of using a gastroduodenal artery graft for reconstruction of the hepatic artery during radical resection of hilar cholangiocarcinoma, which is citation-free and self-contained. In this paper we retrospectively analyzed the clinical data, surgical procedure, and follow-up results in nine patients who underwent hepatic artery reconstruction using a gastroduodenal artery graft during their radical resection of hilar cholangiocarcinoma and no artery thrombosis or other surgical complications were found after operation with minimum follow-up duration of three months. We recommended that a gastroduodenal artery graft was shown to be a good choice for hepatic artery resection after radical resection of hilar cholangiocarcinoma.